Kinetics of monocyte subpopulations during experimental cerebral malaria and its resolution in a model of late chloroquine treatment - Royo, Jade; Camara, Aissata; Bertrand, Benedicte; Batigne, Philippe; Coste, Agnes; Pipy, Bernard; Aubouy, Agnes, the NeuroCM Group; Affolabi, Dissou; Alao, Jules; Ajzenberg, Daniel; Ayédadjou, Linda; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Cerebral malaria (CM) is one of the most severe form of malaria, a neuropathology that can lead to death. Monocytes have been shown to accumulate in brain microvasculature at the onset of the neurological symptoms during CM. Monocytes have a remarkable ability to adapt their function to their microenvironment from pro-inflammatory to resolving activities. This study aimed at describing the behaviour of monocyte subpopulations during infection and its resolution. C57BL/6 mice were infected with P. berghei ANKA and treated or not with chloroquine (CQ) on the first day of neurological symptoms (Day 6) during four days and followed until Day 12 to mimic neuroinflammation and its resolution during experimental CM. LY6C monocyte subpopulations were identified by flow cytometry in the spleen, peripheral blood and brain, quantified and characterized at different time points. In brain, LY6Cint and LY6Clow monocytes were associated with neuroinflammation, while LY6Chi and LY6Cint were mobilized from peripheral blood to brain for its resolution. During neuroinflammation, CD36 and CD163 were both involved via splenic monocytes, whereas our results suggest that low CD36 expression in brain during neuroinflammation phase is due to degradation. The resolution phase was characterized by increased expression of CD36 and CD163 by blood LY6Clow monocytes, higher expression of CD36 by microglia, and a restored high level of expression for CD163 by LY6Chi monocytes present in the brain. Thus, our results suggest that increasing the expression of CD36 and CD163 specifically in the brain during the neuroinflammation phase contributes to its resolution.